Mineralogy and Geochemistry of Black Shale Outcrops at Batu Gajah, Perak - Bin Roslan, Shazrul Hazwan (Universiti Teknologi PETRONAS, 2016)
Recently, black shales have attracted more attentions due to their role as unconventional energy resources. Black shales are widely distributed in both West and East Malaysia. This project focuses on one example of these black shales in Batu Gajah area, Perak. The objective of the project is to characterize the occurrence, geology, mineralogy and geochemistry of these black shales. This report shows the preliminary results of these investigations. Literature reviews on local and international reports and papers indicated increasing the interest in black shales and unconventional energy resources worldwide. It also showed the lack of information about the black shales in Malaysia and Batu Gajah area in particular. The stratigraphy and age of these shales are rather controversy. As part of the work plan of this project, several outcrops of black shales in the Batu Gajah area have been visited, described and sampled. The samples are currently prepared for the next mineralogical and geochemical analyses by drying up the samples and preparing the powders. Part of the samples are also treated to separate the clay fractions by dissolving the carbonate minerals and organic matter. After the samples preparations completed, the mineralogical analyses of both bulk samples and clay fractions will be conducted using XRD. Samples powders will be also analysed for their organic and inorganic geochemistry including TOC and XRF.